Biotechnological Potential of Bdellovibrio and Like Organisms and Their Secreted Enzymes - Bratanis, Eleni; Andersson, Tilde; Lood, Rolf; Bukowska-Faniband, Ewa (Frontiers in Microbiology, 2020)
Bdellovibrio and like organisms (BALOs) are obligate predatory bacteria that selectively prey on a broad range of Gram-negative bacteria, including multidrug-resistant human pathogens. Due to their unique lifestyle, they have been long recognized as a potential therapeutic and biocontrol agent. Research on BALOs has rapidly grown over the recent decade, resulting in many publications concerning molecular details of bacterial predation as well as applications thereof in medicine and biotechnology. This review summarizes the current knowledge on biotechnological potential of obligate predatory bacteria and their secreted enzymes.